KONTRIBUSI KETERAMPILAN MEMBACA APRESIATIF TEKS FABEL TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 30 PADANG - Putri, Melisa; Hafrison, Mhd. (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this research is three. First, describe the reading skills of the text apresitif fable grade VII SMP Negeri 30 Padang. Second, describing the writing skills of text fable grade VII students SMP Negeri 30 Padang. Thirdly, describing the contribution of fable text apreciprocative reading skills to text writing skills Fable class VII SMP Negeri 30 Padang.  This type of research is quantitative by a descriptive method. The design used in this study is design contributions. The population of this study is class VII junior high School 30 Padang registered in the school year 2018/2019, which is as many as 254 students. The samples in this study were determined by proportional random sampling of 20% of the population, which is 56 students. This research Data is in the form of scores of test skills read Fable text appreciative and score test results of text writing fable. The results of this study were three. First, the skill of reading a text apresiative fable grade VII students SMP Negeri 30 Padang is in good qualification (B) with an average value of 74.19. Secondly, the writing skills of text fable grade VII students SMP Negeri 30 Padang are in good qualification (B) with an average of 76.64. Thirdly, there is a contribution of reading skills fable text appreciative to the writing skills of text fable grade VII students SMP Negeri 30 Padang amounted to 51.4%. Kata Kunci: Kontribusi, Keterampilan Membaca Apresiatif, Keterampilan Menulis Teks Fabel